Severe intraoperative hypercarbia undetected by continuous end-tidal CO2 monitoring in a chronic smoker undergoing one-lung ventilation - Shagun Bhatia Shah; Binod Kumar Naithani; Vani Bhageria; Ajay Kumar Bhargava (The Indian Anaesthetists' Forum, 2016)
One-lung ventilation is known to alter the physiology and result in a discrepancy between end-tidal CO2 (ETCO2) and arterial blood CO2partial pressure despite protective mechanisms like hypoxic pulmonary vasoconstriction. Shunts in an emphysematous patient, lateral positioning and capnothorax may aggravate the discrepancy. We present here an incredible discrepancy of 40 mmHg which led us to question the very utility of ETCO2monitoring in this subset of patients and consider alternative techniques.